2021
DOI: 10.3390/ani11071884
|View full text |Cite
|
Sign up to set email alerts
|

Silver and Copper Nanoparticles Inhibit Biofilm Formation by Mastitis Pathogens

Abstract: Bovine mastitis is a common bovine disease, frequently affecting whole herds of cattle. It is often caused by resistant microbes that can create a biofilm structure. The rapidly developing scientific discipline known as nanobiotechnology may help treat this illness, thanks to the extraordinary properties of nanoparticles. The aim of the study was to investigate the inhibition of biofilms created by mastitis pathogens after treatment with silver and copper nanoparticles, both individually and in combination. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 41 publications
2
32
1
Order By: Relevance
“…All of these findings show that raising the AZM concentration had a substantial impact on drug release. These findings are linked to the ease with which AZM can be Equations ( 13) and (14) show that the weight of ZnONP had a considerable favorable influence on drug release after 1 and 3 h in different formulations (9). At constant (X 1 ) and (X 3 ) (0, −1), the percentage of AZM released at the end of 3 h (Y 2 ) was 65.44 ± 2.71 and 75.23 ± 2.75% (D2, D13) at lower and higher ZnONPs weights, respectively.…”
Section: In Vitro Release Study Of Azm-znonpsmentioning
confidence: 97%
See 2 more Smart Citations
“…All of these findings show that raising the AZM concentration had a substantial impact on drug release. These findings are linked to the ease with which AZM can be Equations ( 13) and (14) show that the weight of ZnONP had a considerable favorable influence on drug release after 1 and 3 h in different formulations (9). At constant (X 1 ) and (X 3 ) (0, −1), the percentage of AZM released at the end of 3 h (Y 2 ) was 65.44 ± 2.71 and 75.23 ± 2.75% (D2, D13) at lower and higher ZnONPs weights, respectively.…”
Section: In Vitro Release Study Of Azm-znonpsmentioning
confidence: 97%
“…Equations ( 13) and (14) show that the weight of ZnONP had a considerable favorable influence on drug release after 1 and 3 h in different formulations (9). At constant (X1) and (X3) (0, −1), the percentage of AZM released at the end of 3 h (Y2) was 65.44 ± 2.71 and 75.23 ± 2.75% (D2, D13) at lower and higher ZnONPs weights, respectively.…”
Section: In Vitro Release Study Of Azm-znonpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there are different factors that make AgNPs suitable for use as antimicrobial: (1) It is simple and safe to synthesize on a large scale with low cost [ 16 ]; (2) bacterial resistance to AgNPs is extremely rare; and (3) the surface of AgNPs can be easily modified and synthesized in various shapes [ 17 ]. Several studies have reported that AgNPs have antimicrobial activity against a variety of pathogens, including Salmonella enterica, E. coli O157:H7, Pseudomonas aeruginosa, Listeria monocytogenes, Klebsiella pneumoniae [ 18 ], and mastitis pathogens [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the wet condition of bacteria on the copper surface causes the cell membrane and cytoplasm to be damaged ( 40 ). In addition, the biofilm stretches until it ruptures in direct contact with the nanostructures of the copper nanomesh ( 41 ). After further exposure, the shapes of bacteria on the copper nanomesh became thin, irregular, wrinkled, and coarse, as shown in SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%